Influence of ice templating on oxygen reduction catalytic activity of metal-free heteroatom-doped mesoporous carbon derived from polypyrrole for zinc-air batteries - Kurian, Maria; Ghosh, Meena; Vijayakumar, Vidyanand; Puthiyaveetil, Priyanka Pandinhare; Torris, Arun; Kurungot, Sreekumar (Energy Technology, 2022)
The development of highly active, cost-effective, and durable, noble metal-free oxygen reduction electrocatalysts is inevitable for the full-fledged implementation of fuel cells and zinc-air batteries. This work reports the synthesis of heteroatom (N, P, S)-doped metal-free mesoporous carbon-based electrocatalyst derived from polypyrrole by combining the ice templating, freeze-drying, and carbonization processes. The correlation between the structure and electrochemical activity of the polypyrrole-derived carbon-based electrocatalyst in the presence and absence of ice templating is investigated. The optimized electrocatalyst, aided by the ice-templating and freeze-drying step, shows an onset and half-wave potential (E-1/2) of 0.94 and 0.78 V vs reversible hydrogen electrode, respectively, in an alkaline electrolyte (0.1 m KOH). Later, the application of the optimized electrocatalyst is demonstrated in a primary zinc-air battery (ZAB) cell. The results prove that the ZAB device performance based on the homemade catalyst is on par with that of the state-of-the-art Pt/C cathode. The catalyst performance is correlated with the heteroatom doping and the enhanced porosity of the sample benefitted from ice templating. Ultimately, this work depicts a facile and rational synthesis of a truly metal-free electrocatalyst for the primary ZABs that can be a potential replacement for state-of-the-art systems.
Keywords: metal-free electrocatalysts; oxygen reduction reaction; zinc-air batteries

Insights on prussian blue analogue cathode material engineered with polypyrrole surface protection layer for aqueous rechargeable zinc metal battery - Puthiyaveetil, Priyanka Pandinhare; Nair, Aathira; Dilwale, Swati; Kurian, Maria; Joshi, Kavita; Kurungot, Sreekumar (Small, 2024)
One of the key intricacies against using Prussian blue analogues (PBAs) in aqueous batteries is their gradual dissolution in aqueous electrolytes, resulting in inadequate cycling stability. Besides, the rate capability of PBAs is limited due to their poor electrical conductivity. To overcome these challenges, it is essential to tune the physical and chemical properties of PBAs at the nano regime without affecting the inherent charge storage properties, especially at high-voltage operating conditions. Through this work, a strategy is demonstrated to enhance the electrochemical performance of vanadium-based PBA (V-PBA) by surface engineering using a conducting polymer nano-skin (V-PBA/PPy) for aqueous zinc metal batteries. The polypyrrole (PPy) nano-skin over the V-PBA nanoparticles acts as an electron percolation path to ameliorate the poor electronic conductivity of the otherwise pristine V-PBA. Interestingly, the V-PBA with an optimized polypyrrole coating (V-PBA/PPy-2) exhibits an enhanced specific capacity (173 mAh g-1 at 0.10 A g-1) than the pristine V-PBA counterpart (80 mAh g-1) and 85% capacity retention up to 500 cycles. The DFT calculation confirms the synergistic interaction between PPy and V-PBA and the presence of PPy favors the adsorption of Zn.
Keywords: aqueous rechargeable zinc metal battery; DFT; polypyrrole coating; Prussian blue analogue; surface protection layer